The effect of intra-cerebroventricular injection of insulin on the levels of monoamines on the raphe magnus nucleus of non-diabetic and short-term diabetic rats in the formalin test - Balali Dehkordi, Shima (Iran J Basic Med Sci, 2019)
OBJECTIVE(S): Systemic and intracerebroventricular (ICV) injection of insulin possess analgesic effects. The raphe magnus nucleus (RMN) is part of the endogenous analgesia system. The objective of the present study was to evaluate the effects of ICV injection of insulin on the levels of monoamines and their related metabolites in the RMN during the formalin test in non-diabetic and short-term diabetic rats. MATERIALS AND METHODS: Sixty four adult male rats were used. Diabetes was induced by Streptozotocin (STZ) (60 mg/kg, IP); insulin (5 mU/animal, 5 μl) was injected into the left ventricle. Microdialysis was performed in each rat. Samples were collected at 15 min intervals. After taking the base sample of microdialysis, 50 μl of 2.5% formalin was injected into the plantar surface of the hind paw, and the level of nociception was recorded every 15 sec for 1 hr. Monoamines and their metabolites concentrations were measured using the HPLC-ECD method. RESULTS: Findings showed that ICV injection of insulin in non-diabetic rats increased the concentration of monoamines and their related metabolites in the RMN. In diabetic rats, injection of insulin decreased the concentrations of monoamines and their related metabolites in the RMN (P<0.05). Our results determined that, at least in part, insulin is associated with antinociceptive effect in non-diabetic rats. CONCLUSION: Based on the results, it seems that ICV injection of insulin in non-diabetic rats increased the activity of the central pain control pathways leading to antinociceptive response, but this condition was not seen in diabetic rats.